Effects of different continuous renal replacement therapy patterns on ionized calcium in patients with citrate anticoagulants using calcium-containing replacement solutions: a study protocol - Wan-Li Yan; Shu-Rong Gong; Rong-Guo Yu; Han Chen (Annals of Medicine)
Background It is unclear whether different modes of continuous renal replacement therapy (CRRT) impact post-filter ionized calcium concentrations during regional citrate anticoagulation (RCA) when using calcium-containing replacement fluid.Methods This prospective, single-center, observational cohort study will screen all patients receiving CRRT for eligibility. General clinical information will be collected before commencing CRRT treatment. Patients will be randomly assigned to either the continuous veno-venous hemofiltration (CVVH) or continuous veno-venous hemodialysis (CVVHD) group and switch to the alternative mode in the subsequent treatment session. Pre-filter and post-filter ionized calcium, systemic total and ionized calcium, and effluent total calcium will be measured 2 h after the initiation of CRRT. Electrolyte levels, arterial blood gases, hourly citrate dose, and total citrate dose will be recorded every 6 h until the end of CRRT. The primary outcome is the difference in ionized calcium concentrations at each site over time between the two modes.Discussion This study will build upon clinical practice to explore the differential effects of various CRRT modes on ionized and total calcium in patients undergoing RCA-CRRT with calcium-containing replacement solutions.